(untitled) (Al-Aasar, 2025)
This study examines the situation of women victims of gender-based violence (GBV) in District Multan, analyzing its socio-cultural, economic, and institutional dimensions within the broader context of Pakistani society. The research investigates the forms of GBV, including physical, psychological, sexual, and economic abuse, as well as the social attitudes and structural barriers that perpetuate it. Data were collected through surveys, interviews, and focus group discussions with victims, community members, and key stakeholders. Findings reveal that patriarchal norms, economic dependency, limited legal awareness, and inadequate institutional support significantly hinder women’s ability to seek justice and protection. The study further identifies the role of community stigma, weak law enforcement, and insufficient implementation of protective laws in sustaining the cycle of violence. Based on these insights, strategic recommendations are proposed, including community awareness initiatives, gender-sensitive training for law enforcement, enhancement of victim support services, economic empowerment programs, and stronger enforcement of existing legislation. The aim is to provide evidence-based solutions for policymakers, civil society, and local institutions to effectively address GBV and promote a safer, more equitable environment for women in District Multan and beyond.